On The Gradability of Metaphor - Bierwiaczonek Bogusław (Studies in Logic, Grammar and Rhetoric)
My purpose in this paper is to demonstrate that metaphor should be viewed as a gradable conceptual phenomenon, and to elucidate further the notion of minimal metaphoric mapping between subordinate level concepts dominated by the same basic level category, which I called “syntaphor” in my previous studies. Since the concepts involved in metaphor represent different conceptual distances, metaphor appears to be gradable, starting from the lowest level of syntaphors through the level of close metaphors, to the level of distant and maximally distant metaphors, which have been the focus of interest in most cognitive studies of metaphor so far. In Section 1 I describe briefly an approach to metaphor from the point of view of the theory of categorization, whereby metaphor is defined in terms of mappings between concepts rather than domains. Section 2 presents the notion and four degrees of conceptual distance between the concepts involved in metaphor based on the subordinate, basic and superordinate levels of categorization. In Section 3 four kinds of metaphor are distinguished depending on three degrees of conceptual distance between the source and the target concepts: distant metaphors, close metaphors and syntaphors. The role of syntaphors is further discussed in polysemy and novel metaphors. Some of the crucial aspects of syntaphors are highlighted when they are compared with image metaphors. The most important implications of the study for the theory of metaphor are presented in Conclusions.